Place of Death for Adults Receiving Specialist Palliative Care in Their Last 3 Months of Life: Factors Associated With Preferred Place, Actual Place, and Place of Death Congruence. - Normand, Charles; Johnston, Bridget; Smith, Samantha (My University, 2024)
Objectives: Congruence between the preferred and actual place of death is recognised as an important quality indicator in end- of-life care. However, there may be complexities about preferences that are ignored in summary congruence measures. This article examined factors associated with preferred place of death, actual place of death, and congruence for a sample of patients who had received specialist palliative care in the last three months of life in Ireland. Methods: This article analysed merged data from two previously published mortality follow-back surveys: Economic Evaluation of Palliative Care in Ireland (EEPCI); Irish compo- nent of International Access, Rights and Empowerment (IARE I). Logistic regression models examined factors associated with (a) preferences for home death versus institutional setting, (b) home death versus hospital death, and (c) congruent versus non-congruent death. Setting: Four regions with differing levels of specialist palliative care development in Ireland. Participants: Mean age 77, 50% female/male, 19% living alone, 64% main diagnosis cancer. Data collected 2011-2015, regression model sample sizes: n = 342-351. Results: Congruence between preferred and actual place of death in the raw merged dataset was 51%. Patients living alone were significantly less likely to prefer home versus institution death (OR 0.389, 95%CI 0.157-0.961), less likely to die at home (OR 0.383, 95%CI 0.274-0.536), but had no significant association with congruence. Conclusions: The findings highlight the value in examining place of death preferences as well as congruence, because preferences may be influenced by what is feasible rather than what patients would like. The analyses also underline the importance of well-resourced community-based supports, including homecare, facilitating hospital discharge, and management of complex (eg, non-cancer) conditions, to facilitate patients to die in their preferred place.
Keywords: place of death, location of death, congruence, preference, palliative care (MeSH), end-of-life care (MeSH)